Budgetary constraints faced by local authorities in Zimbabwe. The case of Beit Bridge Town Council - Mulaudzi, Andrew (2017)
The researcher sought to assess the constraints faced by Beitbridge Town Council in the budgeting process. In Chapter one the researcher focuses on the background of the study. Beitbridge Town Council has its set vision, mission, objectives, core-values and goals that guard their daily operations but they were insurmountable constraints being faced in the budgeting process leading to the council failing to meet the set objectives. Research objectives are stated whereby the researcher wants to find out the constraints that are being faced in budgeting. The researcher wanted to find out the responses of Beitbridge town council employees, residence and councillor regarding the constraints being faced and to identify the strategies that are being used to overcome these constraints and how it impacts on service delivery. Researcher justification, limitations and their solutions, delimitations and assumptions are also noted in this chapter. Chapter two reviews on, budgeting systems used in local authorities, constraints encountered in the budgetary process, the link between service delivery and budgeting as well as strategies that can be used to improve budget performance. Chapter three focuses on research methodology which contains the research design, the researcher used both the qualitative and quantitative data gathering techniques. Questionnaires, observations, purposive and random sampling, internal budgeting performance records and interviews were used to gather data by the researcher. The researcher targeted 83% for questionnaires and 17% for interviews. In Chapter four the researcher presents and analyses data findings were the constraints faced in the budgeting process causes of are analysed, responses of Beitbridge Town Councils employees regarding these constraints are also interpreted and the researcher also evaluated if the reasons to poor service delivery by the council was mainly because of poor budget performance. Finally in Chapter five the researcher summarises the whole research and concludes that the major problems faced in budgeting are politically interference, weak internal control systems, ineffective communication, lack of resources and harsh economic conditions. The recommendations of the researcher for Beitbridge Town Council to its budget performance includes improve citizen participation, seek donor funding and improve communication in flows between the council and its residents.